The Effect of Macromedia Flash-based Animation Media on the Discovery Learning Model on the Learning Outcomes of Class XI Science Students of SMAN 5 Makassar - Almur, Faathir; Agussalim, Hastuti; Nur, Andi Bulqiah (MACCA : Science-Edu Journal, 2024)
This quasi-experimental study investigated the impact of using Macromedia Flash-based animation media integrated with the Discovery Learning model on the learning outcomes of Class XI Science students at SMA Negeri 5 Makassar regarding buffer solutions. Employing a posttest-only control group design, the research sampled from a population of eight XI Science classes using random sampling. Class XI Science 1 served as the experimental group, while XI Science 2 was the control group. The experimental group achieved a significantly higher average learning outcome score (80.86) compared to the control group (63.69). Inferential statistical analysis (Mann-Whitney U test, α = 0.05) revealed that while the data was homogeneous, it was not normally distributed. The result (Z_count = 5.56 > Z_table = 1.64) indicates a statistically significant positive effect of the Macromedia Flash-based animation media within the Discovery Learning model on student learning outcomes for the buffer solution topic.